Millibots. - Navarro-Serment, L.E (IEEE Robotics and automation magazine)
Concerns the development of a framework and algorithms for a distributed heterogeneous robot team. Team members exchange sensor information, collaborate to track and identify targets, or even assist each other to scale obstacles. As for sensing, by coordinating its members a team can exploit information derived from multiple disparate viewpoints. A single robot, even though equipped with a large array of different sensing modalities, is limited at any one time to a single viewpoint, but a team of robots can simultaneously collect information from multiple locations. This article describes the design and construction of a team of 7 × 7 × 7-cm robots called "millibots". We show how the team can exploit collaboration to perform missions such as mapping, exploration, surveillance, and eventually support rescue operations.